The 5th Conference on Sustainability in Civil Engineering (CSCE) - Ali, Majid; Javid, Muhammad; Ullah, Shaheed; Ahmad, Iqbal (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The 5th conference on sustainability in civil engineering was held online on August 03, 2023, by the Department of Civil Engineering of Capital University of Science and Technology, Islamabad, Pakistan. The major topics included green construction materials and structures, construction management, and resilient infrastructure and environment. A total of 133 submissions from the UK, Ireland, Canada, Australia, Italy, Cyprus, China, Kazakhstan, Nigeria, Malaysia, KSA, and Pakistan were received. All papers had undergone a comprehensive and critical double-blind review process. In total, 57 reviewers from 16 different countries reviewed papers. In the conference, nine9 speakers delivered keynote lectures, and 56 accepted papers were presented. Civil engineers from academia and industry shared their practical experiences and different research findings.